Pengaruh Kompetensi Pegawai terhadap Kualitas Pelayanan di Kantor Lurah Rakam Kecamatan Selong - Nova Hari Santhi; Abdul Azim Said (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research is a type of quantitative descriptive research, namely a researcher who describes the research variables using a quantitative approach. The population in this study were all employees totaling 17 employees. The sample in this study used a saturated sample, namely the entire population was used as a sample. Data collection used a questionnaire method. The questionnaire method was carried out to obtain respondents' responses regarding the variables of Employee Competence and Service Quality. Data analysis used to test the hypothesis in this study was using Simple Linear Regression analysis found in the SPSS v. 19 program. The results of this study are that Employee Competence significantly influences Service Quality with a positive coefficient, which explains that there is a directly proportional relationship between the two variables. With the Regression Coefficient of the Employee Competence Variable (X) of 0.321, meaning that if X is increased by 1 then Y will increase by 0.321, this shows that the better the employee's competence, the better the quality of service at the Rakam Lombok Timur Village Office. The sig value of 0.038 illustrates that Employee Competence has a positive and significant influence on Service Quality, meaning that the better the Employee Competence, the Service Quality will increase. Service is said to be of quality or satisfactory if the community is satisfied with the service provided and can meet the expectations of the community.